Diagnostic dilemma in a case of obstructive sleep apnoea syndrome with reversible pulmonary hypertension and right heart failure: A case report. (November 2020) - Shiraishi, Haruki; Chida-Nagai, Ayako; Taniguchi, Kota; Abe, Jiro; Izumi, Gaku; Yamazawa, Hirokuni; Ueda, Yuki; Sasaki, Osamu; Miyakoshi, Kosei; Takeda, Atsuhito
Abstract: Childhood obstructive sleep apnoea syndrome (OSAS) secondary to adenoid hyperplasia is known to give rise to pulmonary hypertension. However, we present a case of a toddler with pulmonary hypertension (PH) and right heart failure due to OSAS, the cause of which is difficult to identify. After the patient underwent an adenotonsillectomy, OSAS disappeared and the PH eventually resolved. Both paediatricians and otolaryngologists should know that paediatric OSAS can occur even in the setting of mild, clinically insignificant palatine tonsil hypertrophy and adenoid hyperplasia. Surgical intervention should be considered without losing the opportunity if it could be the cause of PH.